Coronavirus Vaccines in Abundance — What Then? - Dieter Cassel; Volker Ulrich (Wirtschaftsdienst)
Abstract A total of 3.2 million people in Germany have been fully immunised so far. However, in order to achieve herd immunity, which is likely to require an immunisation rate of around 80 % due to the highly infectious mutants, approximately 65 million people need to be vaccinated. The current “imbalance” in the vaccination campaign is largely due to the limited supply of vaccines. Since J&J’s vaccine has recently been approved by the EU and additional production facilities are available, it is foreseeable that the capacities of the vaccination centres will no longer be sufficient. Moreover, at some point the existing unwillingness to vaccinate could become the final bottleneck in reaching herd immunity. This paper provides some calculations for these relationships. Against this background, it is questionable how well-prepared the present system is to cope with these foreseeable problems.